(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The metaphysics of Humean Supervenience has been attacked by two explicitly anti-Humean alternatives: Nomic Realism and Dispositional Essentialism. Each one of these alternatives offers an ontological explanation of the actual distribution of first-order instantiations. They both claim, against the Humean, that this distribution is not a metaphysical accident. In this paper, I argue that the explanations offered by them are illusory.